IMPLEMENTASI QUICK RESPONSE (QR) CODE PADA SAFETY DATA SHEETS (SDS) BAHAN KIMIA UNTUK MENINGKATKAN KESELAMATAN DAN KESEHATAN KERJA DI LABORATORIUM PENDIDIKAN - Adhy Prasetyo; Septiyana Windiastuti (Politek ATK Yogyakarta Press, 2025)
T he Hazardous and Toxic Chemicals have a high risk of causing work accidents in educational laboratories. These accidents are often caused by a lack of understanding of the Safety Data Sheets (SDS). Therefore, it is proposed to implement Quick Response (QR) Code on the SDS of chemicals to facilitate easy access to SDS. Furthermore, chemical users are expected to understand how to use chemicals safely, thereby improving Occupational Health and Safety (OHS). The method for the study is Research and Development (R&D) through data collecting, compiling the summary of SDS, uploading documents, creating QR Codes, printing and attaching QR Codes, testing QR Codes and user surveis. A total of 10 types of chemicals have been implemented with QR Codes and passed the test to access the SDS quickly and easily. The results of the QR Code user survey showed an average satisfaction value of 93%. Based on the results, the implementation of QR Codes on chemical Safety Data Sheets (SDS) is an effective solution to improve Occupational Health and Safety (OHS) in educational laboratories.